Espacio público para el encuentro de la diversidad cultural en Cali comuna 18. (2022)
The project stems from the need to understand what makes a public space generate appropriation in citizenship, thus giving a journey through the history of public space and analyzing the different aspects that compose it, thus defining the importance of cultural diversity in space. public.